Efektivitas Kegiatan Sholat Dhuha Terhadap Pendidikan Karakter pada Siswa MTs Miftahul Ulum Kalirejo - M. Baqir Hidayatulloh; Mohammad Asrori; Parmujianto (EduInovasi: Journal of Basic Educational Studies, 2025)
The influence of globalization has at least touched the character of students, who are currently experiencing such significant changes that it is difficult for the younger generation to face the cultural clashes that lie ahead. Character education is one thing that can be a solution to these problems, character education can increase superior and quality human resources. Character itself is a special characteristic possessed by a person or a nation that has become ingrained into personality. The implementation of character education in schools can of course not only be realized through teaching and learning activities, but can also be built through other self-development programs such as through extracurricular activities and routine activities held at school. This development activity is a very potential way to develop character values ​​in students. In order to develop the character of students at MTs Miftahul Ulum Kalirejo, the Madrasah facilitates students with various kinds of activities in the school environment. Apart from the teaching and learning process in class, activities are also carried out through routine activities, one of which is the Dhuha prayer. The purpose of this routine Dhuha prayer activity is to design students' awareness to have good religious character and spiritual values ​​so that they can be implemented in everyday life.